Het filosofie en vakfilosofie enige betekenis vir beroepsopleiding? - Venter, J. J. (Koers, 1982)
In the light of increasing professionalism and utilitarianism in university training the philosophers and the subject philosophers have the responsibility to indicate the relevance of their fields of endeavour within the framework of training for the professions. The author points out the contribution of these subjects towards the undeniable intellectual enrichment and power of judgement by reference to two professions, viz. those of business manager and of medical doctor. By being professionally supportive Philosophy and subject philosophies can be strengthened by supporting amongst others neglected or under-developed professions by means of a professional philosophy. The fact that the professional world teems with philosophical problems should be brought home not only to colleagues in professional training institutions but also to those who have influence in the professional world itself.